ANALISIS EFISIENSI MANAJEMEN MODAL KERJA DAN RASIO LIKUIDITAS PADA PT ULTRAJAYA MILK INDUSTRY & TRADING COMPANY TBK DAN PT MULTI BINTANG INDONESIA TBK PERIODE 2010–2024 - Nurmailah, Nurmailah; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze and compare the efficiency of working capital management and liquidity ratios between PT Ultrajaya Milk Industry & Trading Company Tbk and PT Multi Bintang Indonesia Tbk during the 2010–2024 period. The research uses a quantitative comparative approach with secondary data obtained from annual financial reports published by each company through the Indonesia Stock Exchange and official company websites. The variables used in this study include Working Capital Turnover (WCT), Current Ratio (CR), Quick Ratio (QR), and Cash Ratio (CaR). The analytical method applied consists of descriptive comparative analysis and financial ratio analysis to evaluate the efficiency of working capital utilization and liquidity performance. The results indicate that PT Multi Bintang Indonesia Tbk tends to have a higher Working Capital Turnover ratio due to efficient inventory and receivable management, while PT Ultrajaya Milk Industry & Trading Company Tbk demonstrates relatively more stable liquidity ratios. The findings show differences in financial management strategies between the two companies in maintaining operational efficiency and short-term obligations. This research is expected to provide insights for investors, academics, and management regarding financial performance evaluation in the food and beverage sector.